2020
DOI: 10.3390/ma13235378
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of Residual Stresses Distribution in Thin-Walled Press-Braked Stainless Steel Sections

Abstract: Stainless steels are increasingly used in construction today, especially in harsh environments, in which steel corrosion commonly occurs. Cold-formed stainless steel structures are currently increasing in popularity because of its efficiency in load-bearing capacity and its appealing architectural appearance. Cold-rolling and press-braking are the cold-working processes used in the forming of stainless steel sections. Press braking can produce large cross-sections from thin to thick-walled sections compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This phenomenon was observed by Dobrzynski et al [ 16 ] while analysing flatness after the face milling process with different strategies. The residual stress distributions created after plastic deformation can be predicted by numerical models or algorithms presented in works by Ding et al [ 17 ], Mutafi et al [ 18 ] and Chen et al [ 19 ]. Sedlak et al [ 20 ] showed that residual stresses are also created after the face milling process.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was observed by Dobrzynski et al [ 16 ] while analysing flatness after the face milling process with different strategies. The residual stress distributions created after plastic deformation can be predicted by numerical models or algorithms presented in works by Ding et al [ 17 ], Mutafi et al [ 18 ] and Chen et al [ 19 ]. Sedlak et al [ 20 ] showed that residual stresses are also created after the face milling process.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, experimental testing results serve to verify the results obtained numerically, e.g., using software based on the finite element method (FEM) [ 35 ]. The above-described strain analysis in the vicinity of the hole drilled in the flat specimen loaded by uniaxial tension, is a typical analysis performed by the finite element analysis (FEA).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have been performed on the influences of initial stress on sheet metal forming. The residual stresses due to the coiling-uncoiling process were specified as the initial stresses in a subsequent FE simulation of cold bending by Quach et al 26,27 and Mutafi et al, 28 and the numerical results were verified to agree closely with laboratory measurements. In our former preliminary research work, 29 the residual stresses and strains at the initial bending position vary with the subsequent loading positions are discussed (see in Figure 1(b)).…”
Section: Introductionmentioning
confidence: 98%